Photopolymerized injectable RGD-modified fumarated poly(ethylene glycol) diglycidyl ether hydrogels for cell growth - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY-V C H VERLAG GMBH, 2008)
In this study, photopolymerized hydrogels of fumarated poly(ethylene glycol) diglycidyl-co-poly(ethylene glycol) diacrylate have been synthesized and modified with cell adhesion peptide, Arg-Gly-Aso (RGD). The structural and mechanical properties of the hydrogels are found to be poly(ethylene glycol) diacrylate (PEGDA) dependent. The percentage of gelation is increased from 72 to 89 wt.% when the amount of the crosslinker co-monomer(PEGDA) in the hydrogel formulation is increased from 20 to 40 wt.%. In the present case, the equilibrium mass swelling is decreased from 216 to 93%. The viscosities of th uncured formulations have also been measured and likewise. the results were influenced by the increasing amount of PEGDA that reduced the value from 83 to 36cp. The compressive modulus of the prepared hydrogels was improved with the addition of the PEGDA, Cell growth experiments have bee performed by comparing the properties of the hydrogels with and without RGD units. The results show that RGD units enhance the adhesion of cells to the surface of the hydrogels. SEM-EDS studies reveal that nitrogen and calcium are produced on the osteoblast-seeded surface of the scaffold within the culture time period.
Keywords: cell growth; hydrogels; photopolymerization; RGD; OSTEOBLAST DIFFERENTIATION; DRUG-DELIVERY; PEG HYDROGELS; TISSUE; BONE; COLLAGEN; PEPTIDE; SCAFFOLDS; KINETICS; ADHESION